Quality of Life in the Elderly People Covered by Health Centers in the Urban Areas of Markazi Province, Iran - Ali Agha nouri; Mahmoud Mahmoudi; Hamide Salehi; Kourosh Jafarian (Sālmand, 2012)
Objectives: To improve quality of life in the elderly through proper plans and active involvement of elderly in their family and community, we should get a lot of information about health-related quality of life because the composition of our population has changed. Infact, the aged population is increasingly growing, that this will, in turn, have an effect on economic progression and well-being in the country. Thus, this study assessed quality of life and its determinants in the people aged 60 years and over living in the urban areas of Central Province.